Kajian Potensi Bahan Bakar dengan Komposisi Sekam Padi Tempurung Kelapa untuk Bahan Baku Biomassa - Andi Saidah; Muktar Sinaga; Amma Muliya Romadoni (Prosiding Seminar Nasional Teknoka, 2023)
Coconut shells and rice husks as alternative raw materials to reduce the use of inorganic energy, from the results of previous research, rice husks have a low calorific value, so to increase the calorific value it is necessary to add other materials that have a better calorific value, other alternatives as The support is coconut shell. The research method was carried out using experimental testing, starting with the burning process to become charcoal, the process of refining the material (mesh), the molding process, and the drying process, the briquette lab test process. In the mixing process, the adhesive material is bran adhesive with a concentration of 1.3. The aim of this test was to analyze the calorific value, water content and amount of ash contained in the briquettes. The research results showed that the calorific value of rice bran husks was 4375.42 Calories/gram, air content 23.43%, dust content 33.79%, and for rice husk coconut shell the calorific value is 5925.96 calories/gram, water content 19.4%, dust content 18.3%